2017
DOI: 10.7717/peerj.3397
|View full text |Cite
|
Sign up to set email alerts
|

The shoaling behavior of two cyprinid species in conspecific and heterospecific groups

Abstract: Mixed-species shoals of fish are frequently found in the field; however, little is known about individual-level interactions within these groups. We examined the collective motion of two cyprinid species (Chinese bream, Parabramis pekinensis, and qingbo, Spinibarbus sinensis) that occupy partially overlapping habitats but differ in social behavior (high vs low aggressiveness) and preferred flow regime (slow vs fast water velocity). We extracted measures of collective motion from video recordings of eight repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…With a few exceptions, species were distinguishable in the videorecordings. Because of the presence of heterospecific schools, the data were not separated by species especially since there is an evidence that the species in the heterospecific groups adjust to each other (Tang et al, 2017). Moreover, size of heterospecific group probably undergoes different pressures and might be more easily dismissed (Wolf, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…With a few exceptions, species were distinguishable in the videorecordings. Because of the presence of heterospecific schools, the data were not separated by species especially since there is an evidence that the species in the heterospecific groups adjust to each other (Tang et al, 2017). Moreover, size of heterospecific group probably undergoes different pressures and might be more easily dismissed (Wolf, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Fish are social organisms and a shoal is often described as a superorganism due to the level of coordination, which is thought to involve inter-fish communication by physical, chemical, or visual signals. 125 127 One explanation which has some merit is the idea that exposure to a small dose of a stressor after rather than before a large dose of the stressor can induce protection. This phenomenon known as postconditioning has been documented 128 , 129 and is thought to be a form of temporal adaptive response possibly involving hormetic mechanisms where the time sequence of the 2 doses is less important than the fact that a small dose is administered.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese crucian carp and 10 groups of 4 qingbo mixed with 5 Chinese crucian carp for stimulus shoal of 9 individuals. The positions of the test fish were analyzed by the automated tracking software program id Tracker (v 2.1) (Pérez-Escudero et al, 2014;Tang et al, 2017). In conspecific dyads, the video files of two of the measurements of 8 vs. 12 in qingbo, three of the measurements of 9 vs. 12 in crucian carp and one measurement of 10 vs. 12 in crucian carp failed to be decoded.…”
Section: Protocol and Setupmentioning
confidence: 99%
“…It is suggested that differences in numerical ability might exist in closely related fish species. This may be reasonable, as qingbo in the field prefer to live in fast-flowing water and exhibit a group-living lifestyle (Killen et al, 2016;Tang et al, 2017).…”
Section: Qingbo Showed Greater Numerical Ability Indicated By Shoal Pmentioning
confidence: 99%